War tourism : Second World War France from defeat and occupation to the creation of heritage - Gordon, Bertram M., 1945- (Cornell University Press, 2018)
"This book addresses the linkages between tourism and war, focusing on tourism by German personnel and French civilians during the Second World War and on postwar memory tourism"--